Integração paisagem-solo e formação cidadã no ensino de Geografia - MATOS, Júlio Rodrigues (2023)
Caratateua Island is made up of fluviomarine sedimentary deposits from the Barreiras Formation. From these formations, the Pleistocene Terraces arise, which are slightly inclined horizontal surfaces with heights of up to 15 meters consisting of soils of the Yellow Latosols class, which are old soils and poor in nutrients, characteristic of the Amazon region. Collections has been carried out at four different points on the island of Caratateua, which has been analyzed in the field, using the Munsell Chart to determine the colors, and field sheet for textural and structural analysis. The perception by the senses were fundamental for the determination of the morphological characteristics. The laboratory analysis was carried out later and allows the teacher to be interdisciplinary with other disciplines from the discussion of the chemical and physical composition of the soil samples, providing the student with a citizenship education with environmental awareness regarding natural resources, since the island it needs public policies that encourage the preservation of its landscape, which is severely weakened in the face of anthropogenic and coastal interference. This process is in accordance with the National Curricular Common Base, a document that integrates the areas of knowledge and has guided public education in Brazil since 2017.